Framing Analysis of Nusantara Capital City on Indonesia Environmental Activist Posts at Instagram - Syafina Azalia (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2025)
Background of the problem: Recently, environmental activists of Indonesia are becoming increasingly aggressive in raising public awareness about environmental issues on social media platforms to highlight environmental problems caused by various factors, including political endeavours. Purpose: The focus of this study is to explore the language choices used in the environmental account’s posts and express their attitudes toward Nusantara Capital City. Method: The data of this study is obtained from one of prominent Indonesia environmental activist account on Instagram, namely greenpeaceid. For highlighting research novelty, this study collects the posts of Nusantara Capital City of Indonesia published from January to September 2024. Moreover, this study uses descriptive qualitative approach to get depth understanding of provided contents. Result: This study result found three ideas conveyed by greenpeaceid post regarding Nusantara Capital City, including rushed development, disregard of environmental sustainability and indigenous rights, and neglect of renewable energy solutions. Moreover, they directly blame the Indonesia government who is not able to thoroughly consider the indigenous people living there for years. Implication: This research significantly contributes primarily to academics or scholars who are interested in framing analysis studies. It is because this study concerns on analysing Environmental issue that is related with political issue in social media.